Analisis Keterkaitan Fintech Innovation, Financial Inclusion, Green Finance, dan Balance of Trade di Indonesia - Budi Rusdianto; Bakhtiar Efendi; Rusiadi Rusiadi; Lia Nazliana Nasution (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research aims to look at the relationship between Fintech Innovation, Financial Inclusion, Green Finance, and Balance of Trade in Indonesia. Financial technology innovation is experiencing very rapid development. Green Finance or a sustainable green economy itself can be interpreted as anything that can be enjoyed not only now but for the long term into the future which ultimately aims to improve the Indonesian economy and play a positive role in the growth of the trade balance. The research method in this research is using the VAR method. The VAR model is a model that is used without emphasizing the problem of exogeneity of the variables used in the analysis. The VAR model makes it easy to provide answers and provide empirical and more complex evidence of the long-term reciprocal relationship of economic variables that contribute to one another. The research results in this study are that the variables are related to each other.